JALAN SUFISTIK IBNU ARABI (MENUJU KESATUAN WUJUD) - Nurhidayat Muh Said (Al-Irsyad Al-Nafs : Jurnal Bimbingan dan Penyuluhan Islam)
Islam is a unitary religion (monotheism) with all aspects of true Islamic teachings and practices showing central and important principles. Sharia itself is a network of mandates and broad rules by connecting the plural world inwardly with a single centre that shows the opposite of the pluralism that surrounds it. In the same way that Islam always tries to match the equality of shapes, patterns and colours with the One, the Central and the Initial, therefore it reflects monotheism in its own way.